One-year outcomes of wide antral cryoballoon ablation guided by high-density mapping vs. conventional cryoballoon ablation for atrial fibrillation: a propensity score–matched study - Chen, Sanbao; Wang, Zulu; Xuan, Fengqi; Liang, Ming; Jin, Zhiqing; Ding, Jian; Sun, Mingyu; Zhang, Ping; Han, Yaling (Frontiers in Cardiovascular Medicine, 2024)
Background: Pulmonary vein isolation (PVI) with wide antral ablation leads to better clinical outcomes for the treatment of atrial fibrillation (AF), but the isolation lesion is invisible in conventional cryoballoon ablation (CB-A). We aimed to investigate the efficacy of the wide pulmonary vein isolation PVI including intervenous carina region guided by high-density mapping compared to pulmonary vein isolation PVI alone without mapping system.We conducted a propensity score-matched comparison of 74 patients who underwent a wide cryoballoon ablation guided by high-density mapping (mapping group) and 74 controls undergoing conventional cryoballoon ablationCB-A in the same period (no mapping group). The primary outcome was clinical recurrence of documented atrial arrhythmias recurrencetachyarrhythmias (ATs) > 30 s during 1-year follow-up.Of 74 patients in the mapping group, residual local potential at pulmonary veinPV antrum was found in 30 (40.5%) patients and additional cryothermal applications were performed to achieve a wide pulmonary vein isolationPVI. Compared with no mapping group, the use of mapping system in the mapping group was associated with longer fluoroscopic time (26.97 ± 8.07 min vs. 23.76 ± 8.36min, P =0.023) and more fluoroscopic exposure (339 [IQR181-586] mGy vs. 224 [IQR133-409] mGy, P = 0.012). However, no significant differences between groups were found in procedure duration and left atrial dwell time (104.10 ±18.76min vs. 102.45± 21.01 min, P =0.619; 83.52 ±17.01min vs. 79.59± 17.96 min, P =0.177). The rate of 12-month freedom from clinical atrial arrhythmiasATs recurrence was 85.1% in the mapping group and 70.3% in the no mapping group (log-rank P = 0.029).Voltage and pulmonary veinPV potential mapping after cryoballoon pulmonary vein isolationPVI can identify residual potential at pulmonary veinPV antrum and additional cryoablation guided by mapping leads to improved freedom from atrial arrhythmiasAF compared to conventional pulmonary vein isolationPVI without mapping system.